2013
DOI: 10.1002/aur.1332
|View full text |Cite
|
Sign up to set email alerts
|

Increased Coherence of White Matter Fiber Tract Organization in Adults with Asperger Syndrome: A Diffusion Tensor Imaging Study

Abstract: To investigate whether there are global white matter (WM) differences between autistic and healthy adults, we performed diffusion tensor imaging (DTI) in 14 male adults with Asperger syndrome (AS) and 19 gender-, age-, and intelligence quotient-matched controls. We focused on individuals with high-functioning autism spectrum disorder (ASD), AS, to decrease heterogeneity caused by large variation in the cognitive profile. Previous DTI studies of ASD have mainly focused on finding local changes in fractional ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
4
16
0
Order By: Relevance
“…While the sample is relatively large compared to the current DWIliterature in ASD, a question can be raised concerning the extent to which the sample represents the general ASD population, as this is first DWI study to include older adults. Moreover, adults with an established ASD diagnosis tend to have lower scores on self-report questionnaires [Bishop and Seltzer, 2012], though our mean AQ-scores match those from a large recent study [Ruzich et al, 2015], and, if reported, from most adult DTI studies [Bakhtiari et al, 2012;Gibbard et al, 2013;Itahashi et al, 2015;Kirkovski et al, 2015;Mueller et al, 2013;Roine et al, 2013]. Some may argue that our sample is mildly affected based on relatively low AQ and ADOS-scores in some participants and IQ-scores above 80.…”
Section: Strengths and Limitationssupporting
confidence: 72%
See 2 more Smart Citations
“…While the sample is relatively large compared to the current DWIliterature in ASD, a question can be raised concerning the extent to which the sample represents the general ASD population, as this is first DWI study to include older adults. Moreover, adults with an established ASD diagnosis tend to have lower scores on self-report questionnaires [Bishop and Seltzer, 2012], though our mean AQ-scores match those from a large recent study [Ruzich et al, 2015], and, if reported, from most adult DTI studies [Bakhtiari et al, 2012;Gibbard et al, 2013;Itahashi et al, 2015;Kirkovski et al, 2015;Mueller et al, 2013;Roine et al, 2013]. Some may argue that our sample is mildly affected based on relatively low AQ and ADOS-scores in some participants and IQ-scores above 80.…”
Section: Strengths and Limitationssupporting
confidence: 72%
“…Prior studies have shown that ASD symptoms reduce with increasing age, but ASD-related impairments do remain pervasive across the lifespan [Perkins and Berkman, 2012]. Moreover, adults with an established ASD diagnosis tend to have lower scores on self-report questionnaires [Bishop and Seltzer, 2012], though our mean AQ-scores match those from a large recent study [Ruzich et al, 2015], and, if reported, from most adult DTI studies [Bakhtiari et al, 2012;Gibbard et al, 2013;Itahashi et al, 2015;Kirkovski et al, 2015;Mueller et al, 2013;Roine et al, 2013]. In addition, it is known that those with a formal diagnosis of ASD in childhood are not always meeting an ADOS cutoff in adulthood [Anderson et al 2014;Fein et al 2013;McGovern and Sigman 2005] and it seems that diagnoses based on a combination of history/caregiver information and clinical observation are significantly more stable over time than results from any single instrument such as the ADOS [Bastiaansen et al 2011;Jones and Lord 2013;).…”
Section: Strengths and Limitationsmentioning
confidence: 44%
See 1 more Smart Citation
“…For example, studies have shown that the last pathways to become myelinated are the frontal and temporal association regions (Kinney et al, 1988). There has been growing awareness of the fact that abnormal white matter development is linked to altered brain connectivity in various neural developmental disorders such as autism, Asperger syndrome, attention deficit hyperactivity disorder (ADHD), idiopathic developmental delays, multiple sclerosis, schizophrenia, sensory processing disorders, and Tourette syndrome (e.g., Nowell et al, 1988; Rapoport et al, 2001; Widjaja et al, 2008; Neuner et al, 2010; Clark et al, 2012; Owen et al, 2013; Roine et al, 2013; Abdel Razek et al, 2014). It is therefore essential to develop a clear picture of the normal patterns and timing of development of brain pathways to accurately assess and diagnose brain disorders during development.…”
Section: Introductionmentioning
confidence: 99%
“…Constrained-spherical deconvolution (CSD) is one of these methods, and is shown to be a robust way to resolve the crossing fiber issue associated with DTI (Farquharson et al, 2013, Tournier et al, 2004, Tournier et al, 2007). In this study, we used a robust global approach (Hsu et al, 2012, Roine et al, 2013) by calculating mean anisotropy and diffusivity measures in the whole brain and CSD-based tractography (Jeurissen et al, 2011) to investigate microstructural abnormalities within two months of mTBI. CSD-based tractography has recently been in use to investigate abnormalities and network alterations following mTBI (van der Horn et al, 2016).…”
Section: Introductionmentioning
confidence: 99%